Parameter Selection of Discrete Particle Swarm Optimization Algorithm for the Quadratic Assignment Problems. (2016) - Pradeepmon, T.G.; Panicker, Vinay V.; Sridharan, R.
Abstract: Quadratic Assignment Problems (QAPs) are the hardest of combinatorial optimization problems, with some problems of sizes of the order of 30 still remaining unsolved optimally. Solving these problems with exact optimization methods is cumbersome and hence the use of non-traditional optimization methods is advisable. The discrete version of Particle Swarm Optimization (DPSO) is a widely accepted non-conventional optimization algorithm for combinatorial optimization problems. This paper uses Taguchi's robust design approach to determine the best combination of parameters for discrete particle swarm optimization algorithm for solving quadratic assignment problems.